Antimicrobial Resistance Profiles and Genes in Streptococcus uberis Associated With Bovine Mastitis in Thailand - Zhang, Tingrui; Niu, Guoyi; Boonyayatra, Sukolrat; Pichpol, Duangporn (Frontiers in Veterinary Science, 2021)
Streptococcus uberis is recognized as an environmental mastitis pathogen in dairy cattle. The reduced success rate of antibiotic treatment for S. uberis intramammary infection may be associated with the antimicrobial resistance (AMR) of these bacteria. This observational study aimed to analyze 228 S. uberis strains associated with bovine mastitis in northern Thailand from 2010 to 2017. AMR and AMR genes were determined by the minimum inhibitory concentration (MIC) using a microdilution method and polymerase chain reaction, respectively. The majority of S. uberis strains were resistant to tetracycline (187/228, 82.02%), ceftiofur (44/228, 19.30%), and erythromycin (19/228, 8.33%). The MIC50 and MIC90 of ceftiofur in 2017 were 2–4-fold higher than those in 2010 (P < 0.01). Resistance to tetracycline and ceftiofur significantly increased between 2010 and 2017 (P < 0.05). The most common gene detected in S. uberis was tetM (199/228, 87.28%), followed by ermB (151/228, 66.23 %) and blaZ (15/228, 6.58 %). The association between tetracycline resistance and tetM detection was statistically significant (P < 0.01). The detection rates of tetM significantly increased, while the detection rates of tetO and ermB significantly decreased during 2010–2017. AMR monitoring for bovine mastitis pathogens, especially S. uberis, is necessary to understand the trend of AMR among mastitis pathogens, which can help create an AMR stewardship program for dairy farms in Thailand.